THE CORRELATOIN BETWEEN KNOWLEDGE AND ECONOMIC LEVELS WITH HIV/AIDS TRANSMISSION PREVENTION BEHAVIOR ON HOUSEWIVES IN MERSI VILLAGE, PURWOKERTO TIMUR SUB-DISTRICT, BANYUMAS REGENCY - Dwindani, Assyifa Tashya; Putri, Prima Maharani; Nitiprodjo, Abdul Hakim; Kusumawati, Anis (E-Jurnal Medika Udayana; Vol 11 No 7 (2022): E-Jurnal Medika Udayana, 2022)
ABSTRACT Background : HIV is still an epidemic for several countries in the world, including Indonesia. The percentage of HIV positive women in Central Java in 2019 was quite high (33.7%) including housewives. Transmission of HIV/AIDS to housewives can occur due to lack of knowledge related to HIV/AIDS. The level of the economy plays a role in influencing a person's behavior in preventing the transmission of HIV/AIDS. Data from the Banyumas Health Office in 2021, reported that there were 62 cases of HIV/AIDS in Banyumas. One of the areas with high HIV/AIDS cases is the Mersi Village area. Objective : This study aimed to determine the correlation between knowledge and economic levels with HIV/AIDS transmission prevention behavior among housewives in Mersi Village, Purwokerto Timur Sub-district, Banyumas Regency. Methods : The study was an analytic-observational study with a cross-sectional approach. Chi-square test and multivariate logistic regression test were utilized to see the bivariate statistical test. Result : Bivariate analysis between knowledge level and HIV/AIDS transmission prevention behavior obtained p value = 0.002 and analysis between economic level and HIV/AIDS transmission prevention behavior obtained p value = <0.001, which meant the p value <0.05 and indicates H1 is acceptable. Conclusion : There is correlation between knowledge and economic levels with the behavior of preventing HIV/AIDS transmission among housewives in Mersi Village, Purwokerto Timur Sub-district, Banyumas Regency. Keywords : knowledge, economy, prevention behavior, HIV/AIDS